Polygonum terzioglui sp. nov. (Polygonaceae), from Northeast Turkey - Makbul, Serdar; Kundakçi, Suzan; Gültepe, Mutlu; Güzel, Murat Erdem; Coşkunçelebi̇, Kami̇l (Phytotaxa, 2023)
Polygonum terzioglui (Polygonaceae), a new species from northernmost part of Turkey, is described based morphological, and molecular evidence. In addition, the leaf, ochrea, and fruit micromorphological traits of the new species are described. All findings revealed that the new species is closely related to P. samsunicum which is endemic to Turkey, but differs in its ochrea divided near the apex, 21 ̶ 27 nerved ochrea, obovate-broadly elliptic leaf, and ovate ̶ narrowly ovate fruit. The current results from the ITS data set also show that P. terzioglui is a member of the sect. Polygonum and separated from its morphologically closest relatives.